PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW BERBANTUAN MEDIA FLASHCARD TERHADAP KEAKTIFAN BELAJAR SISWA SEKOLAH DASAR - Anam, Choiril; Suryani, Ela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Jigsaw-type Cooperative Learning model assisted by flashcard media on elementary school students’ learning activeness. The background of this research is based on the low level of student activeness caused by teacher-centered learning and limited use of learning media. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The research subjects were fifth-grade students of SD Negeri Bergas Lor 01 and SD Negeri Bergas Lor 02. The instrument used was an observation sheet of students’ learning activeness. Data were analyzed using inferential statistical tests. The results indicate that there is a significant difference in learning activeness between students taught using the Jigsaw Cooperative Learning model assisted by flashcards and those taught using the Jigsaw model without flashcards. Therefore, it can be concluded that the Jigsaw-type Cooperative Learning model assisted by flashcard media has a significant effect on students’ learning activeness.